PENGARUH PENGALAMAN KERJA DAN PENEMPATAN KERJA TERHADAP KOMITMEN KERJA KARYAWAN PT. SUMINSURYA MESINDOLESTARI MEDAN - Makmur Lukito; Alfonsius Alfonsius; Chon Cho Reynols Manday (JURNAL BISNIS KOLEGA, 2019)
Abstract. Strict business competition at this time makes the company requires the ability of human resources in running its role in helping companies to improve the performance of the company and its employees as a whole. Work experience and job placement is one of the factors that affect the employees work commitment in a company. The purpose of this study was to find the relationship between work experience and job placement on employee work commitment. Work experience and job placement have a close relationship to improve employee work commitment. Properly organized job placement creates clear goals for employees so they are motivated because they know the benefits of what they are doing. Moreover, employees will do their best if their being rewarded by their employers so as to gain appropriate work experience and continue to develop their performance. The research methodology that is being used to measure is by survey, the type of research is quantitative descriptive and the nature of this research is explanatory research. The populations and samples in this research are all of the employees in PT. Suminsurya Mesindolestari Medan, which are 63 people and in the sampling method using saturated sampling. Data collection method are gone by distributing questionnaires, interviews, and literature studies. Variable was measured by Likert scale. The data analysis model that had been used to answer hypotesis is multiple regression. The results showed that simultaneously both work experience and job placement together significantly affect the work commitment of employees of PT. Suminsurya Mesindolestari Medan, and partially work experience is more affect towards employees work commitment in PT. Suminsurya Mesindolestari Medanthan job placement.Â Keywords: Work Experience, Job Placement, Employee Work Commitment